On the Dramatic Increase with Chain Length of the Oxidazability of Linear Saturated Aliphatic Alcohols on Gold in Alkaline Media - Ureta-Zanartu, M; Mascayano-Collado, C (Elsevier Ltd, 2015)
The electrooxidation of linear saturated aliphatic alcohols from C1 to C8 on gold in alkaline media has been studied by cyclic voltammetry and with an electrochemical quartz crystal microbalance. The current density of alcohol oxidation very markedly increased and, correspondingly, the onset potential decreased, with increasing chain length, that is, with initially slightly increasing, and then constant, pKa. We attribute this oxidazability increase with chain length to the increasing hydrophobicity of the alcohol. Effectively, a molecular dynamics simulation of the hydration of alcohols and alcoholates shows that the hydrophobicity of the alcohols increases with increasing chain length. The higher activity of gold for the oxidation of organic, and also inorganic (CO), compounds in alkaline media is well known, and should be due to an activation of the gold surface by OH adsorption, and not to a change of the compounds themselves, the (majority) neutral alcohol being the oxidized species both in acid and alkaline media. At the potentials at which 1-heptanol oxidation starts, the mass in both base electrolyte and in 1-heptanol is at a minimum, or nearly so, which shows that water is driven away from the surface of gold prior to the oxidation of both gold and 1-heptanol. © 2015 Elsevier Ltd. All rights reserved.